Exploring the pharmacists’ role in optimising antithrombotic therapy in primary care: a qualitative study - Marcel L Bouvy; Vera H M Deneer; Jacqueline G van Paassen; Jaïr P Tan (BMJ Open)
Objective In antithrombotic therapy, the balance between efficacy and safety is delicate, which makes it challenging for healthcare professionals, including pharmacists, to optimise therapy. Pharmacists may play an important role in optimising antithrombotic therapy, but especially in primary care, this role has not been elucidated. Here, we study how community pharmacists (pharmacists in primary care) perceive their current and future role in antithrombotic therapy.Design We conducted a qualitative study using semi-structured interviews. The interview protocol and subsequent analysis were based on the Theoretical Domains Framework, and the findings were interpreted with the Capability Opportunity Motivation – Behaviour System.Setting and participants The interview participants were community pharmacists, located across the Netherlands, from the Utrecht Pharmacy Practice network for Education and Research.Results We interviewed 16 community pharmacists between February and August 2021 and identified several major themes which were important for the pharmacist’s role in antithrombotic therapy. Pharmacists felt responsible for the outcome of antithrombotic treatment and intended to invest in their role in antithrombotic therapy. Pharmacists did, however, experience barriers to their role in antithrombotic therapy, like a lack of access to clinical information such as the indication of antithrombotic treatment and a lack of specific knowledge on this treatment.Conclusion Community pharmacists perceive a role for themselves in antithrombotic therapy. To fulfil this role, several preconditions must be met.